Probing insulin bioactivity in oral nanoparticles produced by ultrasonication-assisted emulsification/internal gelation - Lopes MA (Dove Medical Press, 2015)
Marlene A Lopes,1,2,* Bárbara Abrahim-Vieira,3,* Claudia Oliveira,4,5 Pedro Fonte,6,7 Alessandra M T Souza,3 Tammy Lira,3 Joana A D Sequeira,1,2 Carlos R Rodrigues,3 Lúcio M Cabral,3 Bruno Sarmento,6–8 Raquel Seiça,9 Francisco Veiga,1,2 António J Ribeiro1,4,5 1Faculty of Pharmacy, University of Coimbra, Coimbra, Portugal; 2CNC – Center for Neuroscience and Cell Biology, Coimbra, Portugal; 3Department of Pharmaceutics, Faculty of Pharmacy, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 4I3S, Instituto de Investigação e Inovação em Saúde, University of Porto, Porto, Portugal; 5Group Genetics of Cognitive Dysfunction, IBMC – Instituto de Biologia Molecular e Celular, Porto, Portugal; 6REQUIMTE, Department of Chemical Sciences – Applied Chemistry Lab, Faculty of Pharmacy, University of Porto, Porto, Portugal; 7CESPU, Instituto de Investigação e Formação Avançada em Ciências e Tecnologias da Saúde, Gandra, Portugal; 8INEB – Instituto de Engenharia Biomédica, University of Porto, Porto, Portugal; 9IBILI – Institute of Biomedical Research in Light and Image, Faculty of Medicine, University of Coimbra, Coimbra, Portugal *These authors contributed equally to this work Abstract: Alginate–dextran sulfate-based particles obtained by emulsification/internal gelation technology can be considered suitable carriers for oral insulin delivery. A rational study focused on the emulsification and particle recovery steps was developed in order to reduce particles to the nanosize range while keeping insulin bioactivity. There was a decrease in size when ultrasonication was used during emulsification, which was more pronounced when a cosurfactant was added. Ultrasonication add-on after particle recovery decreased aggregation and led to a narrower nanoscale particle-size distribution. Insulin encapsulation efficiency was 99.3%±0.5%, attributed to the strong pH-stabilizing electrostatic effect between insulin and nanoparticle matrix polymers. Interactions between these polymers and insulin were predicted using molecular modeling studies through quantum mechanics calculations that allowed for prediction of the interaction model. In vitro release studies indicated well-preserved integrity of nanoparticles in simulated gastric fluid. Circular dichroism spectroscopy proved conformational stability of insulin and Fourier transform infrared spectroscopy technique showed rearrangements of insulin structure during processing. Moreover, in vivo biological activity in diabetic rats revealed no statistical difference when compared to nonencapsulated insulin, demonstrating retention of insulin activity. Our results demonstrate that alginate–dextran sulfate-based nanoparticles efficiently stabilize the loaded protein structure, presenting good physical properties for oral delivery of insulin. Keywords: biopolymers, insulin secondary structure, microparticle, molecular modeling, nanoencapsulation processing, oral delivery